Pengaruh Kesiapan Belajar dan Minat Belajar Terhadap Hasil Belajar Pada Mata Pelajaran Ekonomi - Zakiyyan, Ziyan Muhammad Nur; Hermawan, Yoni; Nurdianti, Raden Roro Suci (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The main problem in this study is the low student learning outcomes which are thought to be influenced by learning readiness and learning interest factors. This study aims to analyze the effect of learning readiness and interest in learning on student learning outcomes in Economics subjects in class XI of SMA Negeri 7 Tasikmalaya in the 2024/2025 school year. This research uses quantitative methods with a survey approach. The data collection technique was carried out through distributing questionnaires to students in class XI Social Economics of SMA Negeri 7 Tasikmalaya in the 2024/2025 school year with a total of 186 students selected through purposive sampling technique, and data analysis using multiple linear regression. The results showed that learning readiness and interest in learning had a significant effect on learning outcomes, both partially and simultaneously. The higher the learning readiness and interest in learning of students, the better the learning outcomes obtained. Therefore, it is recommended for schools and educators to improve learning readiness and motivate students' interest in learning through more innovative and interactive learning strategies. Future research can develop this research by considering other factors that contribute to student learning outcomes.